Pink Ribbon (Les Rubans Roses) in Neubourg - Ruel, Juliette (Quality in Sport, 2018)
One woman over eight contracts the breast cancer. The pink ribbon is an international symbol of breast cancer awareness. October is the international month of fight against the breast cancer. At this time, many associations organize almost every time different actions to raise awareness of the prevention and screening of breast cancer. This article is about one sport race in Le Neubourg, one town in Normandie (France) where the association lovingly supports this struggle and gathers people to fight this disease. This article focuses on the Marketing and organization point of view of this sportive event.